THE ROLE OF FINTECH IN IMPROVING FINANCE INCLUSIVE TO DEVELOP MSMEs IN INDONESIA - Sulhan, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Financial technology (Fintech) is a combination of financial management using technology systems. Fintech can be used as a powerful tool to empower MSMEs and encourage national economic growth. By utilizing fintech wisely, MSMEs can increase efficiency, expand market reach and develop their businesses. This journal aims to analyze the role of fintech in increasing financial inclusion for MSMEs in Indonesia. This research uses a literature study approach by observing and analyzing all information and data in depth through various literature, books, notes, magazines, other references related to financial technology, inclusive finance and MSME development in Indonesia. The results of the discussion in this journal show that the presence of fintech has contributed to the development of MSMEs. Not only limited to helping finance business capital, the role of fintech has also expanded to various aspects such as digital payment services and financial regulation. Obstacles to the implementation of fintech in increasing financial inclusion in MSMEs in Indonesia are due to the inadequate distribution of IT infrastructure in Indonesia, the competency of Human Resources related to the application of digital technology which is still weak, weak legislation related to digital transactions and a lack of financial literacy. Finally, strong synergy and cooperation is needed between the government, Fintech companies, MSMEs and the community in developing fintech and inclusive finance to develop MSMEs in Indonesia.